A Study of Relationship Building in the Context of Franchising for A Service Provider - Sakaguchi, Yoshie (2010)
The findings of this research are presented to the business development of a UK-based translation service firm specifically for its strategic marketing plan to enter other markets beyond the current operational scope. Supported by the optimistic future outlook of the UK translation industry and the robust growth of UK franchise market, this research investigates how the franchisors of service industry can establish the productive relationships with the franchisees who are self-motivated and experienced workers. Drawing on the dependence vs. autonomy issues from Franchise Studies and confirmed with the importance of long-term relationship building in business to business context from Relationship Marketing, this study aims to explore the roles of two fundamental relationship constructs, trust and commitment, in controlling over and allowing some autonomy for the franchisee from the franchisors’ point of view. The objectives of the study is achieved by the qualitative research techniques with two main features: the accounts of the purposively selected 6 franchisors whose business nature is similar to that of the translation service provider in question, and interpretive phenomenological analysis which deals with the phenomena detailed by the participants as they are. Main findings are as follows. Trust plays a role of indicators that the franchisees meet quality standard and that the franchisors have the best interest in the franchisees. Commitment means the franchisors’ credit as business as well as the franchisees’ fulfilment of the operation. Although the roles of these two relationship components in allowing autonomy for the franchisees are unsubstantiated, both of them still promote the franchisees’ responsible exercise of their autonomy. In addition, there is divergence in the dimensions of trust and commitment. Based on the findings and discussion the study suggests concrete managerial guidelines which could be useful for the translation service provider to enhance the relationship with the would-be franchisees. To conclude, the limitations of the research are spelled out in relation to the directions for future research.